Mapping the path of the nascent peptide chain through the 23S RNA in the 50S ribosomal subunit. - Stade, K (1995)
Peptides of different lengths encoded by suitable mRNA fragments were biosynthesized in situ on Escherichia coli ribosomes. The peptides carried a diazirine derivative bound to their N-terminal methionine residue, which was photoactivated whilst the peptides were still attached to the ribosome. Subsequently, the sites of photo-cross-linking to 23S RNA were analyzed by our standard procedures. The N-termini of peptides of increasing length became progressively cross-linked to nucleotide 750 (peptides of 6, 9 or 13-15 amino acids), to nucleotide 1614 and concomitantly to a second site between nucleotides 1305 and 1350 (a peptide of 25-26 amino acids), and to nucleotide 91 (a peptide of 29-33 amino acids). Previously we had shown that peptides of 1 or 2 amino acids were cross-linked to nucleotides 2062, 2506 and 2585 within the peptidyl transferase ring, whereas tri-and tetrapeptides were additionally cross-linked to nucleotides 2609 and 1781. Taken together, the data demonstrate that the path of the nascent peptide chain moves from the peptidyl transferase ring in domain V of the 23S RNA to domain IV, then to domain II, then to domain III, and finally to domain I. These cross-linking results are correlated with other types of topographical data relating to the 50S subunit.